A comparative study of the pre-service teachers self-efficacy based on field experience - R. Anthony, Santhanamary; Said, Hamdan (2008)
This study attempts to investigate the selfâ€“efficacy of the student teachers before and after their field experience as to predict their future teaching effectiveness. The study uses a causalcomparative research design. The targeted population consists of 155 preâ€“service teachers from the Institut Perguruan Temenggong Ibrahim. The instruments, â€˜The Teachers Demographic Basic Data Questionnaireâ€™ and â€˜The Teachersâ€™ Sense of Efficacy Scale (TSES)â€™, will be used for collecting data. The Teachers Demographic Basic Data Questionnaire will be field tested to ensure clarity of the questions. The TSES consists of a 24-item scale and the reliability was found to be 0.94. Reliabilities for the subscales of the TSES were found to be â€œ.91 for instruction, .90 for management, and .87 for engagementâ€?. The dependent variable in this research is the teachersâ€™ self-efficacy beliefs whereas the independent variables are the teachersâ€™ demographic factors. The Statistical Package for the Social Sciences (SPSS Windows 13.0) will be used to analyze the data gathered both descriptively and inferentially. In conclusion, understanding the self-efficacy scores of students in teacher preparation programs can be the first step in improving the pool of teacher candidates.